MANAJEMEN DAN PENGEMBANGAN PONDOK PESANTREN - Alfaiz, Baraz Yoechva (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2023)
The community has long realized the role of pesantren because it can produce credible cadres, who not only have potential but can utilize their potential for competence. In this global era, science, culture and the role of pesantren must be more prominent. Pesantren has a reputation as a distinctive Islamic religious institution, especially as an educational institution. Pesantren is also a social institution based on religious values. Currently, one of the problems faced by Islamic boarding schools is the issue of effective and efficient development management. This problem must be overcome by pesantren to improve the quality of education. Therefore, there needs to be good management and development carried out by experienced and knowledgeable Islamic boarding school leaders. The pesantren curriculum is also the most important entity for academic success. Even though we know that pesantren do not have an official curriculum from the government, because it is the policy of every pesantren leader. Therefore, it is necessary to develop a curriculum that is applied to adjust to the times. Based on the results of research that has been carried out the method used is a qualitative method with the type of case study (Case Study). In this study, researchers explained in detail the results of research on the Management and development of Islamic Boarding Schools. The purpose of this study is to analyze the management and development of Islamic boarding schools. It is known that management and development is a very important strategy for Islamic boarding schools, namely as the most important facility for institutions to improve and optimize human resources and curriculum development to achieve the expected goals. Keywords: Management, Development of Islamic Boarding Schools